Case Report: Complete response with combination oncolytic virus immunotherapy in a patient with stage IV renal cell carcinoma—a promising innovative approach - Gesundheit, Benjamin; Brauns, Chaim; Vogl, Thomas J.; Muckenhuber, Alexander; Weisslein, Christine; Schmoll, Harald; Ellis, Ronald; Posen, Yehudit; Raju, Jayadeepa Srinivas (Frontiers in Oncology, 2025)
Metastatic renal cell carcinoma stage IV (RCC-IV) remains a therapeutic challenge, with an overall 5-year survival rate of 12%. Conventional chemotherapy and radiotherapy have shown relatively low efficacy in reducing morbidity and mortality, whereas innovative immunotherapies have demonstrated promising clinical results with fewer adverse events (AEs). Oncolytic virus (OV) immunotherapy has produced remarkable therapeutic effects in many solid tumors, including refractory and end-stage tumors, with intratumoral (IT) injection (IT-OV) suggested to enhance both efficacy and tolerability. We report the clinical course of a patient with RCC-IV who was treated over a period of 3 years with multiple IT injections of various OVs and another immunotherapeutic agent. A complete response—confirmed through periodic radiological surveillance and biopsies—was achieved without any serious side effects, hospital admissions, or surgical interventions throughout the entire treatment course. To our knowledge, this is the first documented case of complete remission of RCC-IV mediated by IT-OV therapy. The rationale and potential of IT-OV therapy as an innovative approach for treating RCC-IV are discussed.